ParVoro++: A scalable parallel algorithm for constructing 3D Voronoi tessellations based on kd-tree decomposition - Wu, Guoqing; Tian, Hongyun; Lu, Guo; Wang, Wei (Parallel computing, 2023)
The Voronoi tessellation is a fundamental geometric data structure which has numerous applications in various scientific and technological fields. For large particle datasets, computing Voronoi tessellations must be conducted in parallel on a distributed-memory supercomputer in order to satisfy time and memory-size constraints. However, due to load balance and communication, the parallelization of the Voronoi tessellation renders a challenge. In this paper, we present a scalable parallel algorithm for constructing 3D Voronoi tessellations, which evenly distributes the input particles between blocks through kd-tree decomposition. In order to construct the correct global Voronoi topology, we investigate both parametric and non-parametric methods for particle communication among the blocks of a spatial decomposition. The algorithm is implemented exploiting process-level and thread-level parallelization and can be used in a diverse architectural landscape. Using datasets containing up to 330 million particles, we show that our algorithm achieves parallel efficiency up to 57% using 4096 cores on a distributed-memory computer. Moreover, we compare our algorithm with previous attempts to parallelize Voronoi tessellations showing encouraging improvements in terms of computation time. •A new parallel algorithm for computing 3D Voronoi based on kdtree decomposition.•Parametric and non-parametric methods for establish communication.•An evaluation of the algorithm, including parallel accuracy and scalability.•A publicly available library (named ParVoro++) implemented as a fork of Voro++.